MINERALOGICAL STUDY OF QSP (QUARTZ-SERICITE- PRYITE) ALTERATION ZONE OF ERDENETIIN-OVOO PORPHYRY Cu-Mo DEPOSIT IN NORTHERN MONGOLIA - YEONGMIN KIM; INSUNG LEE; SODNOM OYUNGEREL; LUVSANCHULTEM JARGAL; TSERENJAV TSEDENBAL (Geological Issues, 2023)
The Erdenentiin Ovoo Cu-Mo porphyry deposit is located in Northern Mongolia near the Erdenet city of the central part of Orkhon province which is 330km away to northwest from Ulaanbaatar. A great part of rock samples collected for this study in Erdenetiin-Ovoo Cu-Mo porphyry deposit are altered granodiorite and diorite, containing ore-bearing quartz veins. QSP (Quartz-Sericite-Pyrite) alteration is well developed in almost all the whole rock samples and the major observed minerals consist of sericite, quartz and pyrite. Main ore minerals are pyrite, chalcopyrite, molybdenite, chalcocite, covellite and sphalerite (Fig. 4). The first three ore minerals are dominant in the deposit. Chalcocite fills the space between pyrite grains or includes other sulfide mineral grains such as pyrite, sphalerite and chalcopyrite, suggesting that chalcocite was precipitated after other sulfide minerals had already formed. Sphalerite grains show relatively high copper contents ranging from 0.95 wt% to 2.9 wt%, whereas copper ore minerals have low or no zinc contents. And chalcocite grain shows 16 ppm gold concentration with low concentration of other elements such as Zn, Fe, As and Mo.